Between globalisation and Brexit: Migration, pay and the road to modern slavery in the UK hospitality industry. Issue 1 (27th April 2018) - French, Steve
Abstract : Neo-liberal economic globalisation has promoted deregulation and a weakening of the role of the state in regulating the national economy. The perceived benefits of competition have been used to justify strategies to reduce operational costs and promote a "race to the bottom". This has led to the development of casualisation strategies, supported by weak labour market regulation, that provide employers with increasing numerical, temporal and pay flexibility. In addition, migration can be utilised by employers to reinforce these strategies. The UK is a prime example of such a neo-liberal state, and labour market practices in the "migrant dense" UK hospitality sector highlight many characteristics of these casualisation strategies. It is argued that these exploitative practices to reduce labour costs also facilitate pathways into modern slavery, where exploitative labour is involuntary and forced. Despite a legal framework to monitor and tackle modern slavery, the problem of resources and political will to enforce this regulation limits the extent to which modern slavery can be challenged, and it is argued that Brexit may create political and economic conditions in which it could thrive.